1998
DOI: 10.1128/jb.180.9.2549-2555.1998
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of a New Cell Wall Hydrolase Gene, cwlF , Which Affects Cell Separation in Bacillus subtilis

Abstract: Bacillus subtilis produces a 35-kDa cell wall hydrolase, CwlF, during vegetative growth. The CwlF protein was extracted from B. subtilis cwlB sigD mutant cells and separated by sodium dodecyl sulfate-polyacrylamide gel electrophoresis. N-terminal amino acid sequencing revealed that its sequence is completely identical to that of the internal region of thepapQ gene product. Disruption of the papQ gene in the B. subtilis chromosome led to the complete loss of CwlF, indicating that papQ is identical tocwlF. CwlF … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
50
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 95 publications
(50 citation statements)
references
References 57 publications
(58 reference statements)
0
50
0
Order By: Relevance
“…In addition, the cell membrane of the elongated cells stained with FM 4-64 apparently exhibited a cell morphology comprising a chain-like structure with septa, but not the filamentous structure that was observed in septation defective cells. The morphology of long chained cells was similar to that of the D,L-endopeptidase-deficient cells (Ishikawa et al, 1998;Ohnishi et al, 1999;Yamamoto et al, 2003; Fukushima et al, 2006), strongly suggesting that IseA overexpression gives rise to a cell separation defect.…”
Section: Isea Overexpression Causes a Cell Separation Defect In Vivomentioning
confidence: 72%
See 2 more Smart Citations
“…In addition, the cell membrane of the elongated cells stained with FM 4-64 apparently exhibited a cell morphology comprising a chain-like structure with septa, but not the filamentous structure that was observed in septation defective cells. The morphology of long chained cells was similar to that of the D,L-endopeptidase-deficient cells (Ishikawa et al, 1998;Ohnishi et al, 1999;Yamamoto et al, 2003; Fukushima et al, 2006), strongly suggesting that IseA overexpression gives rise to a cell separation defect.…”
Section: Isea Overexpression Causes a Cell Separation Defect In Vivomentioning
confidence: 72%
“…A slight difference between them is in the number of the LysM repeats, three for LytE, four for CwlS and five for LytF, respectively, and they have highly homologous catalytic domains (65%~72%). Besides, previous reports revealed that the transcription of the genes of these cell separation enzymes is controlled by RNA polymerases s A and s H for lytE, s D for lytF and s H for cwlS (Ishikawa et al, 1998;Ohnishi et al, 1999;Britton et al, 2002). Although these enzymes have similar domain structures, they are controlled by different s factors and expressed at different times.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These hydrolases can be extracted from the cell wall with a high concentration of LiCl [5,6]. Many cell wall hydrolases consist of two domain structures: catalytic and cell wall binding (CWB) ones [7]. Previously, we reported that the CWB portion of the major autolysin, CwlB(LytC), of B. subtilis binds e¤ciently to the B. subtilis cell wall [8], and recently a fused protein (CWB-LipB) comprising the CWB domain and the B. subtilis extracellular lipase B was localized on the cell surface and found to retain lipase activity [9].…”
Section: Introductionmentioning
confidence: 99%
“…Amidases are the most common cell wall hydrolases and, on the basis of the amino acid sequence similarity in the catalytic domain of amidases, it is possible to divide them into three classes: class I, CwlA, CwlL, XlyA, XlyB, BlyA and a Bacillus sp. amidase; class II, CwlB(LytC), CwlC, CwlD and CwlM; class III, SleBs and CwlJ [6]. Non-catalytic domains are often found in amidases, and some of these domains contain two or three repeated amino acid sequences [47 ].…”
Section: Introductionmentioning
confidence: 99%